Isotopes in Economic Geology, Metallogenesis and Exploration - Huston, David; Gutzmer, Jens (Mineral Resource Reviews, 2023)
This open access book documents the use of radiogenic and stable isotopes to study mineral deposits from a global to the deposit scale. It includes data-sets that have been directly used in mineral exploration. Isotopic data have been key to developing models for the origin of many mineral deposit types. The book has four sections: (1) the use of radiogenic isotopes to date mineral deposits, (2) the use of radiogenic isotope mapping to understand metal sources and regional- to district-scale controls on metallogenesis, (3) the use of light stable isotopes to determine fluid and sulfur sources, and (4) the use of metallic stable isotopes to understand the sources of ore metals. Each section includes chapters on specific isotopic systems and/or mineral systems that provide information on theory, analytical methods, uses in deposit and metallogenic studies, examples, and traps for young players.